Cord blood mononuclear cells prevent neuronal apoptosis in response to perinatal asphyxia in the newborn lamb - Aridas, James D. S. (J Physiol, 2015)
Asphyxia at the time of birth is a significant cause of death or disability in newborns. There is very limited treatment available for these newborns. Autologous umbilical cord blood (UBC) mononuclear cells reduce clinical markers of brain damage following perinatal asphyxia. Autologous UBC mononuclear cells reduce neuroinflammation and neuronal apoptosis within the brain following perinatal asphyxia. Autologous UBC mononuclear cells administered 12 h after perinatal asphyxia are neuroprotective, and a well‐tolerated and feasible treatment for infants following hypoxic ischaemic encephalopathy.